Megaeventos esportivos e políticas de esporte e lazer em Minas Gerais: uma análise a partir do financiamento público. - Adenilson Idalino de Sousa (2021)
The objective of this study was to analyze the financing of public sports and leisure policies in Minas Gerais in the period between 2003 and 2018 - before and after the mega sporting events (2014 World Cup and 2016 Rio Olympic and Paralympic Games) ) and the consequences of this achievement in the execution of public sports and leisure policies in the State. Four (04) multi-year management planning cycles (2004-2018) were analyzed, using the main instruments that guide the planning of public policies at the state level, the Multi-Year Plans - PPAG, the Budgetary Guidelines Law - LDO and the Annual Budget Law - LOA. Data were accessed through the Transparency Portal of the State of Minas Gerais and the ALMG Portal (Legislative Assembly of Minas Gerais). This is a documentary study, with a quantitative and qualitative approach. For the analysis and discussion of the data, the method of analysis of social policies proposed by Boschetti (2009) was used, with attention to the configuration of financing and expenditure, in particular, to the sources of financing, magnitude and direction of expenditure. The study is secured in six parts. Chapter 1: in which the objectives, justification, methodology and motivations of the study are presented; Chapter 2: in which Brazilian federalism is discussed and its relations with sports and leisure policies in the country and in Minas Gerais; Chapters 3 and 4, which present the sports and leisure policies developed in Minas Gerais throughout the study period; Chapter 5, in which the policies developed based on the framework and methodology presented are analyzed, and the final considerations in which those elaborated from the researched data are developed. Among the first of the study, a significant investment was made in sporting mega-events in Minas Gerais, and that this investment did not have a positive impact on public policies for sport and leisure experience in the analyzed periods. Keywords: mega events; sport; leisure; public policy; financing.